Tinkering with nature: discourses of ‘nature’ in media coverage of genetics and biotechnology - Hansen, Anders (2004)
Concepts of nature and the ‘natural’ order of things form a central anchor in public understanding, public debate and controversy about developments in genetic research and in human, animal and plant biotechnology. ‘Nature’, as Raymond Williams observed, ‘is perhaps the most complex word in the language’ and it is precisely from this complexity that its discursive and ideological power is derived. While it is widely accepted that ‘nature’ is a social construct, it is perhaps the chief appearance of not being so, that makes it such a powerful ideological anchor: ‘nature’ in discourse is used to appeal to what is ontological, God-given, the proper order of things, untainted by man, primordial.This article examines the centrality of concepts of nature in public arena controversies about advances in genetic research and biotechnology. The aim is to show how nature is used or invoked to legitimate particular positions in public debate about genetic research and applications. The article explores the uses of nature in British newspaper coverage of genetics and biotechnology, and it examines changes between 1986/87 and 2002/2003.